The Practical Approach of Creating "Unique Selling Proposition" to Boost your Sales and Profits by Positioning your Company as the only Choice in the Market - Miremadi, Alireza (Indian Journal of Marketing, 2010)
Most business people have heard the term Unique Selling Position (USP) bandied about, often when the subject of sales or marketing comes up. Very few understand what it really is, what its significance is on your ability to sell, and most importantly, how to create one. It’s tricky and not something you learn overnight, but it is critical to the success of your business. In order to successfully market your product or service, every business owner needs to focus on what’s special and different about his or her business. Positioning is about making your offering different from, and more valuable than, your competitors’ offerings and placing that idea in the minds of a target group of customers. Positioning attracts customers by creating a positive and unique identity for your company and its offerings. Positioning is vital for distinguishing your offering from everybody else’s. In a world where there are more and more products and services every day, your customers are on an advertising overload all the time. So they pick something to believe and hold that notion until a message breaks through and persuades them to change.